(untitled) (EAAE Annual Conference Proceedings, 2025)
Santarém is a medium-sized city in Portugal where the bullring and the fair defines an emblematic urban space. However, the symbolic importance of this public space does not correspond today to a materialized and recognizable form. The gradual collapse of the activities in the Campo da Feira and the spatial vagueness of the space surrounding the arena building, along with the urban imprecision in defining the city’s limits, are emerging challenges that the city has faced since 1994, then began a process of gradual abandon- ment associated with the relocation of the National Agriculture Fair to the outskirts of the city. This communication aims to highlight an innovative intervention strategy that has made it possible to formulate hypotheses for the reuse of the bullring and the consequent transformation of the old urban space of Campo da Feira in Santarém. It describes the process of applied research, the result of collaboration between the Lisbon School of Architecture and the City Council of Santarém, which, using the tools of urban design and urban morphology, sought to design a diversified public space formal program for the former Campo da Feira, aimed at multiple modes of use and appropriation, both permanent and transitory, or even inter- mittent, but which was rooted in the historical continuity of the city and which valued the pre-existing buildings, adapt- ing them to intense public use. Methodologically, the work was essentially organized into two phases: an initial phase focused on the morphological study of the city, and the main phase, thinking on design, used a series of hypotheses to promote debate and involve the municipal executive and the population in the search for a solution for such an important area for Santarém. The results we propose to present reveal the complexity of the process in design terms and political terms, which led us to opt for a design-based methodology based on typological strategies for reuse and transformation. These strategies are based on four design scenarios that formalize possible, plausible and distinct hypotheses, which allowed us to support the discussion, the political choices to be made, and the main project options to be materialized, rather than a closed project that expressed one final and finished solution.